PROBLEMATIKA PEMBAGIAN HARTA BERSAMA DI SAMALANGA-BIREUEN - Zubaidi, Zaiyad (JURNAL AL-IJTIMAIYYAH, 2019)
Joint assets are assets obtained either individually or with a husband and wife as long as the marriage is underway without questioning registered in the name of anyone. Although the term jurisprudence of shared assets is not found, the community practice does not separate husband and wife's assets in marriage giving birth to a conception of shared assets which is then considered to be syirkah between husband and wife in the institution of marriage. Divorce is one of the causes of the emergence of problems relating to shared property. The problem that is possible is that there is no division in accordance with the provisions of the applicable laws. The question is how to divide shared assets in Samalanga and what is the problem. The research is qualitative research in the form of field studies using a conceptual approach. The results of the study found that in Samalanga-Bireuen there were cases of joint property controlled by one of the wives or husbands, even though the customary practice of the Samalanga community carried out joint property distribution between husband and wife after divorce with a third pattern. This happened because between the husband and wife found that there was still an attitude of apathy and laity towards the existence of shared assets in the marriage.Keywords: Problems, Joint Assets, Divorce.